ESPIRITISMO E CONVERSÃO: FATORES MOTIVACIONAIS DA MIGRAÇÃO RELIGIOSA PARA O ESPIRITISMO, NO BRASIL. - Rodrigues, José do Carmo (2012)
This work performs an analytical study of the religious conversion phenomenon. Particularly, of the factors which motivated the transit of followers of any religion to Spiritism, in Brazil. The groups under study from which new Spiritists originate have been divided in seven blocks: Catholicism, Protestantism, African-Brazilian religions, Umbanda, Asian religions, others and no religion. This analysis favors the social and psychological factors that have led an individual to change religion. By exploring the Brazilian case, this work also approaches the multiplicity of religions, sects, beliefs and religious movements present in the Brazilian scenario, within the dynamics of forces involving this religious sphere. In order to do so, a historical summary of the main religious movements in the Brazilian case is presented. The emphasis is on Spiritism in Brazil and in the world, as a means of characterizing the evolution processes of the Spiritist Doctrine and the arguments with which this Doctrine competes in this mosaic of religious convictions. The research is supported on a questionnaire distributed throughout the national territory, collecting from respondents data that allow us to qualify them under several aspects: income, education, regional location, knowledge and practice of the Spiritist Doctrine, etc. Within the consultation aspects, 18 options are suggested as reasons for the change of religion to Spiritism, and in twenty other aspects, a deepening of the option presented more often in the previous group is offered. The initial options are distributed among the most frequent reasons for religious change observed by the author in personal experience and in literature. The statistic data have been collected from more than two thousand three hundred respondents, in more than 400 municipalities, in all Brazilian states.